If This Street Were Mine… Between Images and Childhoods: maps, tracks and traces of the body-child - Chisté, Bianca Santos; dos Santos, Gabriel Tenório (Revista Brasileira de Estudos da Presença, 2022)
Drawing on the imagetic productions of children playing in the street, this paper discusses the meanings of childhood and the issues surrounding the myths of quietness and immobility of the body to learn, an idea quite present in education. By creating some connections between the images produced by children and the education of care and control, this work proposes a look at the body as power to think other ways of life and to make education with children.